بناء برنامج قائم على برنامج لوفاس وقياس أثره في تنمية مهارة الانتباه لدى أطفال اضطراب طيف التوحد - بن زاوي هدى; غضبان مريم (University of Eloued جامعة الوادي, 2024)
Abstract: The aim of the current study is to build an individual educational program based on the "Lovas" program and measure its effect on developing the "attention" skill for children with autism spectrum disorder. In this study, we use the semi-experimental approach, and the “CARS” scale to diagnose and determine the degree of autism. We use the pre and post test to measure the effect. It was also conducted on a sample chosen in an intentional manner, numbering 10 cases, the age of 4 years, located in the Al-Aidi Center in Wadi Al-Uthmaniyah, Mila Province. The results of the study showed that there is a positive effect of applying the program based on the “Louvas” program in developing the skill of “attention” among children with autism spectrum disorder. The experiment before applying the individual program based on the "Lovas" program and after applying the program. الهدف من الدراسة الحالية هو بناء برنامج فردي تربوي قائم على برنامج "لوفاس" وقياس أثره في تنمية مهارة "الانتباه" لدى أطفال اضطراب طيف التوحد. نستدم في هذه الدراسة المنهج الشبه تجريبي، ومقياس "كارس "لتشخيص وتحديد درجة التوحد، نستخدم الاختبار القبلي والبعدي لقياس الأثر. كما تم إجراؤها على عينة تم اختيارها بطريقة قصدية بلغ عددها 10 حالات أعمارهم 4 سنوات متواجدين بمركز العائدي بوادي العثمانية ولاية ميلة، حيث دلت نتائج الدراسة على وجود اثر إيجابي لتطبيق البرنامج القائم على برنامج "لوفاس" في تنمية مهارة" الانتباه" لدى أطفال اضطراب طيف التوحد، أي توجد فروق ذات دلالة إحصائية عند مستوى الدلالة 0,05 في المتوسطات الحسابية لمهارة (الانتباه) لدى أطفال التوحد بين أفراد المجموعة التجريبية قبل تطبيق البرنامج الفردي القائم على برنامج "لوفاس" وبعد تطبيق البرنامج.
Keywords: انتباه; برنامج فردي تربوي; برنامج "لوفاس"; اضطراب طيف توحد; أثر; attention; individual educational program; "Lovas" program; autism spectrum disorder; impact